2018
DOI: 10.1097/wnr.0000000000000959
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the α5 GABAA receptor to the discriminative stimulus effects of propofol in rat

Abstract: Propofol as an agonist of GABAA receptor has a rewarding and discriminative stimulus effect. However, which subtype of the GABAA receptor is involved in the discriminative stimulus effects of propofol is still not clear. We observed the effects of an agonist or an antagonist of the subtype-selective GABAA receptor on discriminative stimulus effects of propofol. Male Sprague-Dawley rats were trained to discriminate 10 mg/kg (intraperitoneal) propofol from intralipid under a fixed-ratio 10 schedule of food reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
5
9
0
Order By: Relevance
“…Our results clearly demonstrate that propofol is capable of mediating reinforcement in self-administration studies, consistent with previous studies [6][7][8]. We found that lower doses of MK-801 (0.1-0.2 mg/kg) were able to increase propofol self-administration infusion numbers in a dose-dependent fashion in rats without impacting general locomotor activity, in line with previous ndings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results clearly demonstrate that propofol is capable of mediating reinforcement in self-administration studies, consistent with previous studies [6][7][8]. We found that lower doses of MK-801 (0.1-0.2 mg/kg) were able to increase propofol self-administration infusion numbers in a dose-dependent fashion in rats without impacting general locomotor activity, in line with previous ndings.…”
Section: Discussionsupporting
confidence: 93%
“…Both conditioned place preference and self-administration studies in animals have further con rmed that propofol can provide reinforcement [3][4][5]. We have previously demonstrated a role for GABA receptors in the ventral tegmental area (VTA) as regulators of propofol self-administration behavior [6]. We further found that the D1R antagonist SCH23390 was able to mediate a simultaneous dose-dependent reduction in propofol selfadministration while also decreasing D1R-associated p-ERK/ERK levels in the nucleus accumbens (NAc) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Our results clearly demonstrate that propofol is capable of mediating reinforcement in selfadministration studies, consistent with previous studies [6][7][8]. We found that lower doses of MK-801 (0.1-0.2 mg/kg) were able to increase propofol self-administration infusion numbers in a dosedependent fashion in rats without impacting general locomotor activity, in line with previous findings.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, MK-801 can mediate the partial inhibition of progressive ERK activation in the NAc and dorsal striatum of rats following acute Δ9tetrahydrocannabinol (THC) administration, while SCH23390 fully blocked this response [42]. We have previously found the D1 dopamine receptors to be linked with ERK activity in the NAc in the context of propofol self-administration [7,8] . This suggests that NMDAR activity is likely a mediator of propofol self-administration responses, with dopamine signaling being dominant and glutamate signaling playing a secondary role in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation